Tribes Without Rulers : Studies in African Segmentary Systems. - Middleton, John (Taylor and Francis, 2013)
Recent research in Africa has shown a wide range of political systems, from small societies of wandering hunters to large states of several million people comparable with mediaeval European feudal kingdoms. In between are many societies in which a central government is lacking; the political system is based upon a balance of power between many small groups, which with their lack of classes or specialized political offices, have been called 'ordered anarchies'. First published in 1958.